2002
DOI: 10.1073/pnas.0237083100
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-induced cellular stress and p53 activation in chronic inflammation

Abstract: Free radical-induced cellular stress contributes to cancer during chronic inflammation. Here, we investigated mechanisms of p53 activation by the free radical, NO. NO from donor drugs induced both ataxia-telangiectasia mutated (ATM)-and ataxiatelangiectasia mutated and Rad3-related-dependent p53 posttranslational modifications, leading to an increase in p53 transcriptional targets and a G2͞M cell cycle checkpoint. Such modifications were also identified in cells cocultured with NO-releasing macrophages. In non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
239
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 330 publications
(258 citation statements)
references
References 42 publications
15
239
0
4
Order By: Relevance
“…The tumor suppressor p53 protein plays an important role in DNA repair, cell cycle arrest, and apoptosis (46,74). Induction of apoptosis is considered to be central to the tumor suppressive function of p53.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor p53 protein plays an important role in DNA repair, cell cycle arrest, and apoptosis (46,74). Induction of apoptosis is considered to be central to the tumor suppressive function of p53.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed inflammatory syndromes have been shown to cause cells in the vicinity of lymphocyte invasions to undergo a p53 response. 79,80 Communication may occur in the other direction with p53-regulated exosomes signaling to T cells and immunizing the organism with parts of damaged cells. These ideas suggest the exploration of whether p53 plays a role in the recovery from infectious diseases, inflammation or the initiation of autoimmunity or the establishment of tolerance?…”
Section: Questions About the P53 Pathway In A Larger Contextmentioning
confidence: 99%
“…Also, iNOS was strongly observed in inflamed epithelium. Earlier studies have shown that iNOS is expressed in epithelial cells in patients with colitis who are prone to colon cancer (48)(49)(50). Regarding the link between iNOS and cancer development, the expression of iNOS was higher in cancer specimens than in normal tissue in esophageal, colon, and thyroid carcinomas (51, 52).…”
Section: Mol Cancer Res 2008;6(2) February 2008mentioning
confidence: 99%